Case studies leading to the management of tunnel fire risks during TBM drives in an old coalfield. (June 2021) - Bilgin, Nuh; Balci, Cemal; Aslanbas, Ali
Highlights: Two most disastrous fire in Turkish coal fields are criticized. The management of tunnel fire risks in the ground contaminated by petroleum products is discussed with two case studies. The management of tunnel fire risks in coal field when driving with EPB TBMs is discussed. A case study when diving a tunnel in a coalfield in Istanbul is summarized. Abstract: Much of the research studies carried out in the past on tunnel fires are related to completed tunnels, i.e. when the tunnels are in operation. Although worldwide mechanized tunnel excavations are increasing every year, not much work is seen on the fire safety issues related to the construction of such tunnels. At the other end, the introduction of plows and shearers in mining with cutting power of more than 1000 kW and associated equipment like panzers and belt conveyors started in the mid-1960s. As a consequence, the need to evaluate the effect of this new technology on fire hazards in explosive gas medium emerged, leading to detailed research works which also helped to manage tunnel fire risks during tunnel boring machine (TBM) drives. In the light of experiences gained on methane/dust explosions, conveying belt fires in Turkish Coal Mines, and fires generated thereafter, guiding principles of managing the risk of tunnel fires during TBM excavations are developed and are discussed in this paper. Special attention is attired to two EPB TBMs excavating in the new Istanbul Airport Metro project under risk of methane explosion. Another source of tunnel fires in urban areas is the soil contamination by unexpected leakage of petroleum products which need special risk management programs during tunnel excavation using mine safety regulations. Determination of the safety risks and precautions taken in two cases on such grounds are also discussed in detail in this paper.